(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe knowledge and attitudes of health students at Dai Nam University about monkeypox in 2022. Methods: Cross-sectional study. Results: The study was conducted on 661 students of the Faculty of Medicine, the Faculty of Pharmacy and the Faculty of Nursing, Dai Nam University using a pre-designed questionnaire to describe students’ knowledge and attitudes about monkeypox. The results showed: the rate of gaining knowledge about monkeypox was 56.4%. The percentage of students with a positive attitude about monkeypox was 52%. Conclusion: The rate of gaining knowledge about monkeypox as well as the percentage of students with positive attitude about the disease is low. Therefore, the school administration needs to take positive and specific measures to contribute to improving students’ knowledge and attitudes about monkeypox.